Спектрофотометрическое исследование кометы Вест 1975n (1976VI). Натрий в голове кометы - Таращук, В.П. (Известия Крымской астрофизической обсерватории, 2007)
The old spectrophotometric observations of comet 1976 VI West are presented. The main emission features in the head of comet in energy units are given. The problem of radiating of sodium emission and its formation from comet dust is discussed.